Level of Knowledge of Early Detection of Breast Cancer in USU Faculty of Medicine Students, 2018–2019 - Nadira Afia; Denny Rifsal Siregar (Talenta Publisher, 2023)
Background: Breast cancer is a malignant tumor that grows in breast tissue can come from components such as fat tissue, blood vessels. Early detection is one of the breast cancer prevention efforts that can help reduce the incidence of breast cancer. There are three ways to prevent breast cancer including primary prevention, secondary prevention and tertiary prevention. Objective: To determine the level of knowledge regarding breast cancer prevention among students of the Faculty of Medicine, Universitas Sumatera Utara for the 2018–2019 academic year. Methods: This study uses a descriptive type of research with a cross-sectional approach. The population in this study amounted to 495 students and the sample to be carried out in this study was 83 students of the Faculty of Medicine, Universitas Sumatera Utara 2018–2019 who met the inclusion criteria. Data analysis used univariate analysis with frequency distribution table. Results: The level of knowledge of USU Faculty of Medicine 2018–2019 students was 61.5% good, 38.5% sufficient, and there were no students who had a low level of knowledge. Conclusion: Most medical students at the Universitas Sumatera Utara have a good level of knowledge about breast cancer prevention. This indicates a generally adequate awareness, which is essential for early detection and effective prevention efforts.